Delayed complication due to retained contrast following augmented pressure distal loop colostogram in anorectal malformation - Mahendra Kumar Jangid; Jitendra Sharma; Roshan Chanchlani; Rajesh Malik; Reyaz Ahmad (Wolters Kluwer Medknow Publications, 2022)
Augmented-pressure distal loop colostogram (APDC) is the most important diagnostic investigation to delineate the detailed anatomy to plan the reparative management of anorectal malformations. APDC is generally considered safe, with a very low complication rate. Herein, we present an unreported complication of APDC, manifesting as acute abdomen, due to retained contrast in distal loop. The patient was managed with evacuation of retained contrast from distal loop. We recommend evacuating the contrast from the distal loop following APDC.